Strengthening Tribal Livelihoods Through Development Funds: A NABARD Intervention Case Study in Nagaland - Varghese, Andrea; Sundari, R. Guna (Journal of Social Science and Humanities, 2026)
Tribal Development Fund (TDF) is one of NABARD’s supported programmes aimed at improving the livelihood opportunities of tribal people through integrated farming approach. The tribal communities are the most underprivileged section of the Indian society. NABARD aims to uplift the tribal communities by improving the quality of life through better access to education, healthcare, drinking facilities and provision of other basic amenities. The study is based on Nagaland, a state in the North East Region (NER) of India where majority of the rural people are primarily dependent on agriculture as a source of livelihood. The paper is an attempt to study the impact of the TDF programme in improving the economic conditions of the tribal people in Nagaland. The study uses t - test to determine the intervention impact of the programme. Findings of the study conclude that there is visible improvement in the lives of the tribal people through TDF intervention programme of NABARD.